2009
DOI: 10.1182/blood-2008-12-193524
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the urokinase receptor in neutrophil efferocytosis

Abstract: The urokinase receptor (uPAR) plays an important role in regulation of fibronolysis, cell migration, and adhesion. In this study, we examined whether uPAR plays a role in modulating efferocytosis of neutrophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 51 publications
3
62
1
Order By: Relevance
“…Notably, the urokinase plasminogen activator receptor has recently been described as a novel engulfment receptor (20), although its prophagocytic role remains controversial (21). Moreover, Das and Plow (22) have described the histone 2B-dependent recruitment of plasminogen to PS-rich surfaces, and it has been shown that PAI impairs apoptotic cell removal (23).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the urokinase plasminogen activator receptor has recently been described as a novel engulfment receptor (20), although its prophagocytic role remains controversial (21). Moreover, Das and Plow (22) have described the histone 2B-dependent recruitment of plasminogen to PS-rich surfaces, and it has been shown that PAI impairs apoptotic cell removal (23).…”
Section: Discussionmentioning
confidence: 99%
“…Partly in contrast with these results, Park et al demonstrated increased macrophage efferocytosis of apoptotic neutrophils when uPAR was knocked-out, either in the neutrophil or the macrophage, but interestingly not when knocked-out in both cell types [109]. A wide range of integrins were shown to be involved in this unilateral uPAR effect and the increased efferocytosis was reversed when exogenous suPAR was added to the experimental system [109]. The incomplete concordance of these studies can possibly be explained by differences between species as well as the cell types being professional versus non-professional phagocytes.…”
Section: Efferocytosis -The Quiet Elimination Of Dying Cellsmentioning
confidence: 72%
“…In line with these results, there is another study reporting increased uptake of apoptotic T cells in uPAR overexpressing cancer cell lines [108]. Partly in contrast with these results, Park et al demonstrated increased macrophage efferocytosis of apoptotic neutrophils when uPAR was knocked-out, either in the neutrophil or the macrophage, but interestingly not when knocked-out in both cell types [109]. A wide range of integrins were shown to be involved in this unilateral uPAR effect and the increased efferocytosis was reversed when exogenous suPAR was added to the experimental system [109].…”
Section: Efferocytosis -The Quiet Elimination Of Dying Cellsmentioning
confidence: 77%
See 2 more Smart Citations